Elaboration of a situational strategic planning in an oncology outpatient clinic: experience report. (Research, Society and Development, 2022)
Objective: to report the experience on the elaboration of a situational strategic planning in an oncology clinic and formulate action strategies to address the main problems encountered. Methodology: Descriptive study, of the experience report type, carried out by nurses and doctors in an outpatient clinic of an oncology hospital. It was used as a methodological support for the accomplishment of the study the problematization from the Arch of Charles Maguerez, in which five stages were covered, aiming at the quality and methodological rigor, they are: I) Identification of the Problem, II) Key point; III) Theorization; IV) Hypothesis and V) Application in reality. Results: objectives and goals were raised to try to solve the identified problem, provided through the experimentation of reality and thus achieve results, above all, educational, which are as follows: objectives: improve professionals' knowledge about institutional protocols and improve the technological support of the hospital. The defined goals were: to promote continuing education for the multiprofessional team and to create a mapping protocol for users who use the outpatient service. Conclusion of the study: The intervention in reality, through planning actions with scientific basis, aiming at the best solution to the identified problem, was benefited by the methodologically designed actions and services, given that there was multiprofessional participation and articulation throughout the process of action, contributing substantially to strengthen a line of comprehensive and resolute care with user satisfaction and professional contemplation.